Isolation and Characterization of Flavonoid from Methanolic Extract of Mirabilis jalapa Linn. Tuber and Evaluation of its Cardioprotective Property - Shil, D.; Dash, S.; Laloo, D.; Dasgupta, D. (Asian Journal of Chemistry, 2018)
The aim of the study is to isolate and characterization of bioconstituent present in methanolic extract of Mirabilis jalapa L. tuber and also evaluate the cardioprotective property of the extract as well as isolated compound from the extract. The bioactive constituent flavonoid was isolated from methanolic extract through flash chromatography technique by using solvent system ethyl acetate and methanol. The chemical structure of compound was confirmed on the basis of spectroscopy analysis and identified as 2-(3′, 4′-dihydroxy phenyl)-3,5,7- trihydroxy chromen 4-one. Administration of Mirabilis jalapa extract in higher dose 200 and 400 mg/kg b.w. and isolated compound to doxorubicin-intoxicated rats demonstrated prominent reduction in serum biomarker enzymes, normalization of serum lipid profiles. Also, significant modulation of malondialdehyde (MDA), endogenous non-enzymatic (GSH) and enzymatic (SOD and CAT) antioxidant and detoxification systems compared to doxorubicin control rats. This was achieved due to presence of flavonoid in the methanolic extract of Mirabilis jalapa L. tuber.